Psychological Problems of Learning From Home During Covid-19 Pandemic in Early Childhood - M. Syukri Azwar Lubis; Hotni Sari Harahap; Armanila armanila (Institut Agama Islam Negeri Langsa, 2021)
The COVID-19 pandemic has caused the face-to-face learning system to switch to learning from home. This transition makes parents have to adapt to these new circumstances. This study aims to determine the psychological problems of learning from home during COVID-19 in early childhood. This qualitative research with a case study approach involves parents of children aged 5-6 years, schools, and the community in Paya Geli Village, Sunggal District, Deli Serdang Regency, North Sumatra Province. Data were obtained through interviews, observation, and documentation techniques. Data analysis uses the Miles and Huberman model, including data reduction, display, and verification. The results of this study found several problems, namely: 1) Parents became stressed so that violence occurred in teaching. 2) Children become passive, uncreative, unproductive due to stress. 3) gadgets have become a place for children to escape to avoid stress. Thus, it is hoped that parents will be wiser in teaching their children at home to minimize the occurrence of psychological problems learning from home.